Experimental analysis and characterization of abrasive water jet machining of Inconel 718. (2020) - Bhandarkar, Vivek; Singh, Virendra; Gupta, T.V.K.
Abstract: The present work is machining of Inconel 718 material by abrasive water jet machining technique. The work aims to understand the role of traverse speed and pressure in obtaining the required dimensions and also to characterize the machined surface to avoid any cracks while machining. The first part of work is to optimize the feature dimensions and the later part is on characterization using scanning electron microscope (SEM). The responses are the feature dimensions like length, breadth, depth and surface roughness, where regression analysis has been carried with S/N ratios using MINITAB16 software. It is observed that abrasives are impregnated on the machined surface at low traverse speeds and scratches are detected which leads to poor finish.